The HTA of genomic applications in Italy: methodological and organisational preparedness. (20th October 2021) - Migliara, G; Pitini, E; Baccolini, V; Isonne, C; Mazzalai, E; Salerno, C; Turatto, F; De Vito, C; Marzuillo, C; Villari, P
Abstract: Background: The formal process to determine the value of a health technology is Health Technology Assessment (HTA). Two key components are required to implement the HTA of genomic applications: the development of a specific methodology and an adequate network. This work aims to review the state of HTA in Italy and to assess its preparedness for genomic applications, both at a national and regional level. Methods: For the national level, a narrative review of the policy documents regulating the HTA process was conducted. For the regional level, an update of a previous survey on the topic (SIHTA/AGENAS 2016) was performed through the search and analysis of regional websites, and grey and scientific literature. Results: Various national centres share a role in the governance of the HTA process and/or in the production of reports, such as the National Agency for Regional Healthcare Services (since 2006), the Steering Committee of the Italian National HTA Program for Medical Devices and the National centre for HTA (since 2017). 76% of the Regions has specific regulations for the HTA process. Of these, 68.8% regulate the reporting phase, 62.5% the priority setting, 81.3% the assessment, 50% the appraisal, and 43.8% the dissemination. The following dimensions were assessed: "technical characteristics", "health problem and current use", "cost and economic effectiveness" by 62.5% of the Regions; "efficacy", "safety", "organizational aspects" by 56.3%; "ethical aspects" by 25%; "social aspects", and "legal aspects" by 18.8%. Conclusions: The HTA is specifically addressed at a National level, but there is an overlap of institutional roles in its governance. At regional level, while most Regions have HTA specific regulations, there is great heterogeneity among them in the phases regulated and in the dimensions evaluated. Moreover, there is a lack in evaluation of dimensions essential for a comprehensive assessment of genomic applications, like ethical, social and legal aspects". Key messages: Policy documents on HTA are well developed and integrated in the governance of the NHS. However, there seems to be a dispersion of value with various centres partially overlapping in their functions. There is a lack of evaluation in dimensions fundamental for genomic tests, due to the implications of privacy violations, impact on quality of life and abuses that can follow these tests.